PENENTUAN KADAR FRUKTOSA HASIL HIDROLISIS INULIN DENGAN DNS SEBAGAI PENGOKSIDASI: PENENTUAN KADAR FRUKTOSA HASIL HIDROLISIS INULIN DENGAN DNS SEBAGAI PENGOKSIDASI - Ruswandi Ruswandi (EKSAKTA: Berkala Ilmiah Bidang MIPA, 2018)
The content of fructose that produced by hydrolysis of inulin can be easily and practically determined by DNS reagent. The aim of this study is to determine the optimum condition of reaction between fructose and DNS reagent for determining the content of fructose produced by hydrolysis of inulin. The equipment used in this study are spectronic 20 D and HPLC. The mobile phase that used in HPLC is ethanol:water with various ratio. The column that used in this study ODS C-18, C-8 and CLC-Sil. The recation between fructose and DNS reagent has λmaks 499 nm, the optimum volume of fructose solution is 100 μL, the optimum pH of fructose is 4.5 and the stability time of color of reducted DNS is in the minutes of 30th . The result of reducted DNS analysis using HPLC doesn’t give the good separation at column ODS C-18 and CLS-Sil with several variations of mobile phase of ethanol:water. The contents of fructose that produced by hydrolysis of inulin with 0,5%, 1% and 2,5% concentrations of inulin are 183.6 μg/mL, 295.6 μg/mL and 512.6 μg/mL.